Incidências do desejo materno nas possibilidades de recuperação do bebê prematuro. - Torres, Cynthia Marden (2009)
Based on previous clinical experiences with premature babies at the Lauro Wanderley´s University Hospital, a systematic research is proposed to contribute towards the Frej Project- Limits, Boundaries and Addressing code between mother and child. The aim is to study mother and child addressing code theme, focusing on motherhood desire accounts due to medical team interventions as well as its prospective effects on premature child recovery assisted in neo-natal intensive care unit. Both male and female premature babies will be assessed at such intensive unit. Attention will be given to the interaction with their mothers and or with the medical crew of the abovementioned hospital. The babies will be assessed by means of the Esther Bick method, which will be adapted according to each case. The clinical observation will be evaluated, taking into account the theoretical psychoanalytical point of reference of this research project. The study material will be categorized and qualitatively analyzed according to both the Esther Bick method and other researchers of psychoanalytic premature clinic. The main elements of observation will be the voice, the look, feeding associated with the interventions of the medical crew. It is expected that the results might broaden the horizon of the understanding of mother and risk bearing premature child relationship, with emphasis towards the subjective aspects of such early moment of life.